2002
DOI: 10.1182/blood.v99.2.409
|View full text |Cite
|
Sign up to set email alerts
|

Proteins encoded by genes involved in chromosomal alterations in lymphoma and leukemia: clinical value of their detection by immunocytochemistry

Abstract: IntroductionTranslocations, deletions, and other nonrandom chromosomal abnormalities 1,2 play a central role in the pathogenesis of many human hematologic malignant diseases. A growing number of studies are revealing the ways in which these chromosomal alterations affect specific genes, such as those encoding nuclear transcription factors. However, any gene implicated in the neoplastic process can act only through the protein it encodes. Many of the consequences of chromosomal changes with respect to abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
147
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 243 publications
(195 reference statements)
1
147
1
7
Order By: Relevance
“…1 Although NPM is known to shuttle back and forth between the nucleus and the cytoplasm, 2 only a minimum amount of the protein is present at any time in the cytoplasm; this explains why with immunohistochemistry NPM is only detectable at the nucleolar level. 3 We previously showed that NPM is aberrantly expressed in the cytoplasm of anaplastic large cell lymphoma cells carrying t(2;5), due to the presence of the NPM-ALK fusion protein. 3 Ectopic NPM expression parallels that of ALK protein and serves as a highly specific diagnostic test on routine biopsies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although NPM is known to shuttle back and forth between the nucleus and the cytoplasm, 2 only a minimum amount of the protein is present at any time in the cytoplasm; this explains why with immunohistochemistry NPM is only detectable at the nucleolar level. 3 We previously showed that NPM is aberrantly expressed in the cytoplasm of anaplastic large cell lymphoma cells carrying t(2;5), due to the presence of the NPM-ALK fusion protein. 3 Ectopic NPM expression parallels that of ALK protein and serves as a highly specific diagnostic test on routine biopsies.…”
mentioning
confidence: 99%
“…3 We previously showed that NPM is aberrantly expressed in the cytoplasm of anaplastic large cell lymphoma cells carrying t(2;5), due to the presence of the NPM-ALK fusion protein. 3 Ectopic NPM expression parallels that of ALK protein and serves as a highly specific diagnostic test on routine biopsies. 3 The t(3;5)(q25;q35) is a rare chromosomal translocation which is detected in myelodysplastic syndromes and acute myeloid leukaemia (AML), 4 more frequently of FAB-M6 type.…”
mentioning
confidence: 99%
“…46 Nevertheless, the view that the NPM1 moiety of the chimeric protein only provides a dimerization substrate for the C-terminal onco-protein has recently been challenged by in vivo evidence that NPM1 is an haploinsufficient tumour suppressor gene. 55 Therefore, its heterozygous loss could also contribute to the pathogenesis of the disease.…”
Section: Nucleophosmin Traffic Is Perturbed In Lymphomas and Leukaemimentioning
confidence: 99%
“…Because of its ALK moiety, at least a proportion of the NPM1-ALK protein anchors to ALCL cell cytoplasm. 46 This accounts for the aberrant cytoplasmic expression of nucleophosmin that is revealed with antibodies against the NPM1 N-terminus (which is retained in the fusion protein). 46,49 In contrast, NPM1wt that can be detected with an antibody against NPM1 C-terminus (that is not retained in NPM1-ALK), maintains its expected nucleolar expression in ALCL with t(2;5), 49 suggesting that localization is not perturbed by the NPM1-ALK fusion product.…”
Section: Nucleophosmin Traffic Is Perturbed In Lymphomas and Leukaemimentioning
confidence: 99%
See 1 more Smart Citation